Knowledge and attitude towards mental illness among the nurses of BPKIHS. - K.C., Smriti (2012)
ABSTRACT: Mental disorders are widely recognized as a major contributor to the global burden of the disease worldwide. Mental health is a crucial component but still a marginalized and neglected area. Nurses are first line of health workers who have to deal very closely with mentally ill patient. This study was conducted to assess the knowledge and attitude towards mental illness among the nurses of BPKIHS. Descriptive cross sectional design was adopted for the study. A total of 150 samples were identified using population proportionate, systemic random sampling technique. Data were collected by using pretested, self developed, semi-structured and self-administered questionnaire. Data were analyzed using descriptive and inferential statistics. The p-value was calculated to find significance of variables. The study results revealed that the median percentage of knowledge of the respondents regarding mental illness was 73.077% and that of attitude was 72.667%. Only, 7% of the respondents had received CNE/training on mental illness. Majority (64.7%) of the respondents had adequate knowledge whereas half (50%) of the respondents had favorable attitude. It was found that knowledge regarding mental illness was significantly associated with educational level (p= 0.005), experience working with patients having mental illness (p=0.012) and duration working with mentally ill patients (p=0.041). Also, attitude towards mental illness was significantly associated with educational level (p= 0.031) and experience working with patients having mental illness (p=0.017). As, this study revealed that knowledge and attitude towards mental illness are positively significantly correlated among the nurses, positive attitude towards mental illness can be developed by reducing the stigma and demystification of prevailing misconceptions with the implementation of various awareness program (CNE/ISE/training) on mental illness. Key words: Knowledge, Attitude, Mental illness, Nurses